Clinical repercussions of the therapeutic use of cannabis derivatives in rheumatoid arthritis and osteoarthritis (Research, Society and Development, 2022)
Introduction: Chronic inflammatory conditions related to joints are a source of intense daily suffering. The reduction in the life quality of its patients and the working capacity of some are related to intense pain and deterioration of the tissues that compose the cartilage by cells of the immune system. Cannabinoids have gained considerable relevance as objects of study regarding their vast applicable properties to pharmacological therapies, including anti-inflammatory and analgesic effects. This article aims to analyze the academic production on the implication of the use of cannabinoids as therapy in rheumatoid arthritis and osteoarthritis. Methodology: 5 articles were selected from the Virtual Health Library, published between 2017 and 2021, to compose this Integrative Literature Review. Discussion: In particular, cannabidiol has been shown to act upon receptors that participate in cellular pathways related to pain regulation and that delay the destructive process of affected tissues. The use of Cannabis derivatives for therapeutic purposes has gained great adherence, especially in countries where there is already legislation which allows it, especially by people living with chronic neuropathic pain. Conclusions: Pain control is the most emphasized symptom in the literature, due it’s impact on life quality of those affected. There is great interest from the scientific community in the advancement of cannabinoid study techniques. In parallel, people affected by diseases that could possibly benefit from cannabinoids therapeutic effects have sought them as an alternative to regularly prescribed drugs.